Prelacteal feeding among infants within the first week of birth in eastern Uganda: evidence from a health facility-based cross-sectional study - Racheal Akello; Derrick Kimuli; Stephen Okoboi; Alimah Komuhangi; Jonathan Izudi (BMC, 2021)
Abstract Background Prelacteal feeding hinders early initiation of breastfeeding and exclusive breastfeeding but is understudied in Uganda. We examined the prevalence and factors associated with prelacteal feeding among postpartum mothers in Kamuli district in rural eastern Uganda. Methods We conducted a cross-sectional study between December 2020 and January 2021 at four large healthcare facilities and randomly sampled mother-baby pairs attending postnatal care and immunization clinics. Prelacteal feeding was defined as giving anything to eat or drink to a newborn other than breast milk within the first 0-3 days of life. Data were collected using a researcher-administered questionnaire and summarized using frequencies and percentages. The Chi-squared, Fisher's exact, and Student's t-tests were used for comparison while the factors independently associated with prelacteal feeding were determined using modified Poisson regression analysis, reported as an adjusted prevalence risk ratio (aPRR) with corresponding 95% confidence intervals (CI). Results Of 875 participants enrolled, 319 (36.5%) practiced prelacteal feeding. The likelihood of prelacteal feeding was lower among participants who were unemployed (aPRR 0.70; 95% CI 0.5, 0.91), married (aPRR 0.71; 95% CI 0.58, 0.87), had received health education on infant feeding practices (aPRR 0.72; 95% CI 0.60, 0.86), had a spontaneous vaginal delivery (aPRR 0.76; 95% CI 0.61, 0.95), had delivered in a health facility (aPRR 0.73; 95% CI 0.60, 0.89), and who knew that prelacteal feeding could lead to difficulties in breathing (aPRR 0.70; 95% CI 0.57, 0.86). Conversely, prelacteal feeding was more likely among participants who had attended antenatal care at a public health facility during the most recent pregnancy (aPRR 2.41; 95% CI 1.71, 3.39) and those who had travelled more than 5 km to a health facility for postnatal care services (aPRR 1.46; 95% CI 1.23, 1.72). Conclusions The prevalence of prelacteal feeding among postpartum mothers in rural eastern Uganda is slightly higher than the national average. Accordingly, there is a need to continuously educate mothers and staff on infant feeding practices to tackle the factors influencing prelacteal feeding and promote appropriate infant and young child feeding practices as emphasized in the baby-friendly health facility initiative policy.